1
$\begingroup$

Let $...E_3\subset E_2 \subseteq E_1$ be a decreasing sequence and $\mu(E_i)<\infty$ then $\mu(\cap E_n)=lim(\mu(E_n))$

I know that there is a prove based on $\mu(\cup E_n)=lim(\mu(E_n))$ for increasing sequence but I want to understand the following proof (if it has not errors)

$$\mu(E_1\setminus\cap E_n)=\mu(E_1)-\mu(\cap E_n)\iff\mu(\cap E_n)=\mu(E_1)-\mu(E_1\setminus\cap E_n)=_{(1)}$$

$$=_{(1)}\mu(E_1)-\mu(E_1\setminus\cup E_n^C )=\mu(E_1)-\mu(\cup (E_1\cup E_n^C ))=$$

$$=\mu(E_1)-\mu(\cup (E_1\setminus E_n))$$

How did we go from $(1)$ and forward? shouldn't it be

$$\mu(E_1)-\mu(E_1\setminus\cap E_n)=_{(1)}\mu(E_1)-\mu(E_1\setminus(\cup E_n^C)^C )$$

$\endgroup$
2
$\begingroup$

There is a small typo in the first step after (1), which should explain it. We have

$$E_1\setminus \cap E_n = E_1\setminus(\cup E_n^c)^c= E_1\cap (\cup E_n^c) = \cup (E_1\cap E_n^c).$$

Does that help?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.